Dialectical Film Criticism: Walter Benjamin’s Historiography, Cultural Critique and the Archive - Russell, Catherine (Transformations, 2007)
Walter Benjamin suggests that the past “only comes into legibility” in the present. Several of Benjamin’s more familiar terms, such as the flaneur, dialectical optics, the collector and the gambler, may likewise be applied to the practice of historical film criticism. In this paper Benjamin’s historiography is developed as a method of film criticism. The renewed access to film history made possible by new digital technologies has opened up new modes of film criticism that draw on the archive of film history. This paper will draw on Benjamin’s Arcades Project in conjunction with the film studies concepts of “vernacular modernism” (Miriam Hansen) and film melodrama, in addition to theoretical frameworks provided by Giorgio Agamben, Jürgen Habermas. Benjamin’s diverse and unsystematic writings, in my view, provide important tools for writing film criticism that is “against the grain.” The sense of urgency and impending political crisis –and the utopian potential of image culture – that are embedded in his view of modernity are no less relevant to contemporary society, and his criticism is a reminder of the critical values that are embedded in popular culture and in image culture on a larger scale. Film examples in the paper include the narrative cinema of Naruse Mikio, the documentary film Heir to an Execution, and the experimental film Kristall.